2016
DOI: 10.1039/c6bm00459h
|View full text |Cite
|
Sign up to set email alerts
|

Strontium folate loaded biohybrid scaffolds seeded with dental pulp stem cells induce in vivo bone regeneration in critical sized defects

Abstract: Strontium folate (SrFO) is a recently developed bone promoting agent with interest in medical and pharmaceutical fields due to its improved features in comparison to current strontium based therapies for osteoporosis and other bone diseases. In this work SrFO derivative was synthesized and loaded into biohybrid scaffolds obtained through lyophilisation of semi-interpenetrating networks of chitosan polyethylene glycol dimethacrylate and beta tri-calcium phosphate (βTCP) fabricated using free radical polymerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…Taking into account all those results, Martin-Del-Campo et al developed a biohybrid scaffold of tricalcium phosphate (TCP), which was loaded with SrFO and seeded with human dental pulp stem cells [16]. They demonstrated that it enhanced the osteogenic differentiation of these cells and promoted bone formation in a rat calvarial defect model (Figure 2B).…”
Section: Discussion: B-vitamins As a Tool In Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account all those results, Martin-Del-Campo et al developed a biohybrid scaffold of tricalcium phosphate (TCP), which was loaded with SrFO and seeded with human dental pulp stem cells [16]. They demonstrated that it enhanced the osteogenic differentiation of these cells and promoted bone formation in a rat calvarial defect model (Figure 2B).…”
Section: Discussion: B-vitamins As a Tool In Tissue Engineeringmentioning
confidence: 99%
“…( B ) Micro-computed tomography images of cranial defects treated with TCP and TCP/SrFO scaffolds at 4, 12 and 20 weeks and defect closure on the side of the implants form the coronal plane (arrows) and 3D images (circles) ( 1 ) and bone density of the radiographic density (HU) in cranial defects ( 2 ) (* p < 0.001). Figure 2B is reproduced from [16] with permission from the Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…Martin-del-Campo et al loaded the SrFO derivatives in TCP and chitosan polyethylene dimethacrylate scaffolds, which were then seeded with DPSCs. They observed significantly improved results with SrFO-integrated scaffolds in terms of bone formation [212]. In a clinical study by Al Ahmady et al, autologous bone marrow mononuclear cells combined with platelet-rich fibrin and nanohydroxyapatite were used to treat alveolar cleft.…”
Section: Cell Therapymentioning
confidence: 99%
“…60 Further, a cement precursor was found composed of 58 wt% a-tricalcium phosphate, 24 wt% calcium hydrogen phosphate, 8.5 wt% hydroxyapatite and 8.5 wt% strontium carbonate and later mixed with a 4% aqueous disodium hydrogen phosphate solution to assist new bone formation in Sprague-Dawley rats, 61 and silicon (Si) and Zn doped brushite cements (BrCs) alone and in combination with insulin like growth factor 1 (IGF-1), coming to four different scaffolds: (IGF-1) BrC, (IGF-1) Si-BrC, (IGF-1) Zn-BrC, and (IGF-1) Si/Zn-BrC cements, on New Zealand white rabbits. 62 Moreover, scaffolds from very different compositions were found: SrO doped biosilicate scaffolds, fabricated by mixing Mg 2 SiO 4 and CaSiO 3 and adding SrO in different ratios, being 0SrO (0 wt%), 0.5SrO (0.5 wt%), 1SrO (1 wt%), 2SrO (2 wt%), and 3SrO (3 wt%), were used to treat MG-63 cells; 63 a zinc silicate mineral coated PLLA scaffold compared to a non-coated scaffold and tissue culture plastic (TCPS), cultured with adipocyte derived stem cells (ADSCs); 64 a strontium chloride (SrCl 2 ) coated porcine femur cancellous bone derived scaffold (CPB) subsequently coated with polycaprolactone (PCL) obtaining CPB/Sr/ PCL on hMSCs; 65 a sol-gel method synthesized hybrid scaffold incorporating: phosphate ions, calcium from calcium dichloride (CaCl 2 Á2H 2 O) and Sr from strontium dichloride hexahydrate (SrCl 2 Á6H 2 O) was incorporated into human osteoblast cell line (HOB) cultures; 66 a Sr folate (SrFO) loaded bio-hybrid porous scaffold obtained by interpenetrating beta tricalcium phosphate (bTCP) and polyethylene glycol dimethacrylate networks in contrast with a bTCP scaffold, which was used in an experiment in human dental pulp stem cells (HDPSCs) as well as in vivo in Wistar rats; 67 Wharton's jelly-derived mesenchymal stem cells (WJCs) were treated with either a rod-like nano hydroxyapatite (RN-HA) or a flake-like micro hydroxyapatite (FM-HA) as a coating for a Mg-Zn-Ca alloy scaffold in another study; 68 a Collagen type-I (Col-I) coated magnesium-zirconia (Mg-Zr) alloy, containing different quantities of Sr, where the scaffolds were divided into 3 samples: No-Sr, Low-Sr (1.82 wt%) and High-Sr (4.8 wt%) and later implanted into New Zealand white rabbits; 69 another Sr containing HA/polylactide composite group with four scaffolds was obtained: CT (control, Sr0/polylactide), SrL (Sr0.5/polylactide), SrM (Sr5/polylactide) and SrH (Sr50/polylactide), which were as well implanted into New Zealand white rabbits; 70 and lastly, three different studies chose to use a calcium silicate based bio-ceramic that contains Sr and Zn ions: strontium-hardystonite-gahnite (Sr-HT-gahnite) scaffolds, [71][72][73] since it has been recently studied due to its biocompatibility and exclusive microstructure (Fig. 2).…”
Section: Tissue Engineering Based On Zn and Sr Containing Scaffoldsmentioning
confidence: 99%